An Infinite-Horizon Model of Dynamic Membership of International Environmental Agreements - Santiago Rubio; Alistair Ulph (Fondazione Eni Enrico Mattei (FEEM), 2003)
Much of the literature on international environmental agreements uses static models, although most important transboundary pollution problems involve stock pollutants. The few papers that study IEAs using models of stock pollutants do not allow for the possibility that membership of the IEA may change endogenously over time. In this paper we analyse a simple infinite-horizon version of the Barrett (1994) model, in which unit damage costs increase with the stock of pollution, and countries decide each period whether to join an IEA. We show that there exists a steady-state stock of pollution with corresponding steady-state IEA membership, and that if the initial stock of pollution is below (above) steady-state then membership of the IEA declines (rises) as the stock of pollution tends to steady-state. As we increase the parameter linking damage costs to the pollution stock, initial and steady-state membership decline; in the limit, membership is small and constant over time.
Keywords: F02; F18; Q20; 330; Self-enforcing international environmental agreements; Internal and external stability; Stock pollutant; Umweltabkommen; Mitgliedschaft; Grenzüberschreitende Umweltbelastung; Spieltheorie; Kooperatives Spiel